EFFECT SKIN EXTRACT OF LAUREL BARK (Syzygium polyanthum) AND EXTRACT OF GUAVA BARK (Psidium guajava L) TO SINKING SPEED YARN PA (Polyamide) - Olivia, Yulia Dini; Rengi, Pareng; ', Isnaniah (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted in March 2015 in the Material Fishing Device Laboratory, Faculty of Fisheries and Marine Sciences, University of Riau, Pekanbaru. The aim of this research was to determined the influence of the speed of sinking yarn PA (Polyamide) which has been preservatied with extract of laurel bark and extract of guava bark. The method in this research was experiments that carried out in the Laboratory Material Fishing Device Faculty of Fisheries and Marine Sciences, University of Riau, Pekanbaru by observing the speed of sinking yarn PA (Polyamide) which uses preserveted extract of laurel bark extract and extract of guava bark with the same concentration which 0.7 kg/pliter of water. Each treatment was repeated 10 repetitions. From the sinking speed measurement data the thread can be seen that the value of the highest drowning rate is on a extract of laurel bark to the value of 1.8054 cm/sec, followed by extract of guava bark with a value of 1.5622 cm/sec, the thread of control with a value of 1.3502 cm/sec.Keywords: Sinking Speed, Laurel bark, Guava bark, PA (Polyamide) Yarns